الأساس الديني والتكوين المذهبي ودوره في الصراع العثماني الفارسي - عيجولي, حمزة (جامعة الوادي - University of Eloued, 2018)
After the collapse of the Almohads’s state in 1269, many states appeared in the geographical scope of the Islamic World, east and west, seeking to obtain religious legality that would guarantee respect and acceptance, to which the Ottoman and the Safavid states are considered perfect examples. The Ottoman state that started as a bedouin principality in Anatolia rapidly gained momentum and developed into a vast empire, considered itself as the vanguard of the Islamic Caliphate. With the advent of the Safavid state that had started as a religious little family on an Iranian hill and expanded outside Iran relying on religious grounds, adopting the Shi’ite doctrine to differentiate itself from its neighbor and rival, the Ottoman empire, the two states engaged in a bitter political and military conflict; a factional conflict that became an essential variable in the Ottoman-Persian dispute for centuries.
مقال
Keywords: الدولة العثمانية، الدولة الفارسية، الصراع الديني